Stent stoma: Endoscopic stent insertion for refractory small intestine fistulas - Kantowski, Marcus; Sauer, Peter; Ardelt, Michael; Melling, Nathaniel; Roesch, Thomas; Zhang-Hagenlocher, Christine (Scandinavian journal of surgery, 2025)
Background and aims: The therapeutic management of fistulas presents significant challenges, often involving both conservative and surgical approaches. Despite these interventions, recurrence and postoperative mortality rates remain high. Endoscopic stent insertion into the fistula, along with the creation of a stent stoma, may offer a promising alternative for patients who fail surgical or conservative therapies. This study aimed to evaluate the feasibility, effectiveness, and safety of endoscopic stent insertion in the treatment of refractory small intestinal fistulas.Methods: Patients with refractory small intestine fistulas who underwent endoscopic stent insertion were included. The primary endpoint was defined as successful fistula treatment, which included an improvement in clinical symptoms related to the fistula, successful bridging to subsequent surgical revision, and the restoration of enteral nutrition. Secondary endpoints comprised the feasibility of the endoscopic procedure, complications, procedure-related complications, and in-hospital mortality.Results: Eight patients were included, with a median follow-up period of 2.7 months. The implantation of a self-expanding metal stent was successfully performed in all patients (technical success rate, 100%; n = 8/8). The clinical success rate was 87.5% (n = 7/8), indicating clinical improvement in fistula-related symptoms, wound care, and enteral nutrition. Procedure-related complications occurred in one patient (12.5%; n = 1/8), involving stent dislocation leading to small intestine perforation, which was managed endoscopically. No procedure-related mortality was observed.Conclusions: Endoscopic stent insertion is a feasible, effective, and safe option for the management of therapy-refractory small intestinal fistulas. The creation of a stent stoma improves patient quality of life.
Gesehen am 15.01.2026